2010
DOI: 10.1089/acm.2009.0177
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of the Effect of Methyl B12 Treatment on Behavioral and Biomarker Measures in Children with Autism

Abstract: Comparison of the overall means between groups suggests that methyl B12 is ineffective in treating behavioral symptoms of autism. However, detailed data analysis suggests that methyl B12 may alleviate symptoms of autism in a subgroup of children, possibly by reducing oxidative stress. An increase in glutathione redox status (GSH/GSSG) may provide a biomarker for treatment response to methyl B12. Additional research is needed to delineate a subgroup of potential responders and ascertain a biomarker for response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 18 publications
2
69
0
2
Order By: Relevance
“…One prior small randomized, placebo-controlled trial of methyl B12 in 30 children with ASD did not find statistically significant improvements in the overall Clinical Global Impressions (CGI) score; however, a subset of children (9/30) showed clinically significant improvements in the CGI and improvements in glutathione levels, again suggesting that improvements in the antioxidant defense might lead to improvements in symptoms (Bertoglio et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…One prior small randomized, placebo-controlled trial of methyl B12 in 30 children with ASD did not find statistically significant improvements in the overall Clinical Global Impressions (CGI) score; however, a subset of children (9/30) showed clinically significant improvements in the CGI and improvements in glutathione levels, again suggesting that improvements in the antioxidant defense might lead to improvements in symptoms (Bertoglio et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In the B12 randomised controlled trial by Bertoglio et al (2010) reported side effects were increased hyperactivity and increased mouthing of objects. No serious adverse events were reported.…”
Section: Vitamin B12mentioning
confidence: 99%
“…As a result, caregivers may elect to implement CAM interventions to treat or prevent nutritional deficiencies. Oxidative stress (Villagonzalo et al 2010) Deficiency (Clark et al 1993;Steinemann &Christiansen 1998;Ming et al 2005) Reconnect retinoid receptor pathways (Megson 2000) Immunomodulation (Megson 2000) Antioxidant ( Gut dysbiosis and inflammation results in decreased GI synthesis of B12 and/or absorption (Kidd 2002b;Erickson et al 2005) Trans-methylation and trans-sulphation pathway abnormalities Bertoglio et al 2010) causing oxidative stress (Villagonzalo et al 2010) Normalise B12 levels Correct folate/methionine metabolite profile and other indexes of oxidative stress James et al 2009;Bertoglio et al 2010) www.intechopen.com Trans-methylation pathway abnormalities Bertoglio et al 2010) causing oxidative stress (Villagonzalo et al 2010) Neurotransmitter level abnormalities (Lam et al 2006) Correct folate/methionine metabolite profile and other indexes of oxidative stress James et al 2009 Neurotransmitter level abnormalities (Lam et al 2006) Folate/methionine pathway abnormalities Bertoglio et al 2010) Oxidative stress (Villagonzalo, et al 2010) Immunoadjuvant (Graber et al 1981) Modulate neurotransmitters (Kern et al 2001) Methyl donor (Kern et al 2001) Antioxidant (Kern et al 2001) General autistic behaviours Vitamin C Neurotransmitter level abnormalities (Lam et al 2006) Oxidative stress (Villagonzalo et al 2010) Immune system dysfunction (Goines&Van de Water 2010)…”
Section: Nutritional Deficienciesmentioning
confidence: 99%